Development of the four-item Letter and Shape Drawing test (LSD-4): A brief bedside test of visuospatial function. (January 2017) - Williams, Olugbenga Alaba; O'Connell, Henry; Leonard, Maeve; Awan, Fahad; White, Debbie; McKenna, Frank; Hannigan, Ailish; Cullen, Walter; Exton, Chris; Enudi, Walter; Dunne, Colum; Adamis, Dimitrios; et al.
Abstract: Conventional bedside tests of visuospatial function such as the Clock Drawing (CDT) and Intersecting Pentagons (IPT) lack consistency in delivery and interpretation. We compared performance on a novel test of visuospatial ability - the LSD – with the IPT, CDT and MMSE in 180 acute elderly medical inpatients [mean age 79.7±7.1 (range 62–96); 91 females (50.6%)]. 124 (69%) scored ≤23 on the MMSE; 60 with mild (score 18–23) and 64 with severe (score ≤17) impairment. 78 (43%) scored ≥6 on the CDT, while for the IPT, 87 (47%) scored ≥4. The CDT and IPT agreed on the classification of 138 patients (77%) with modest-strong agreement with the MMSE categories. Correlation between the LSD and visuospatial tests was high. A four–item version of the LSD incorporating items 1, 10, 12, 15 had high correlation with the LSD-15 and strong association with MMSE categories. The LSD-4 provides a brief and easily interpreted bedside test of visuospatial function that has high coverage of elderly patients with neurocognitive impairment, good agreement with conventional tests of visuospatial ability and favourable ability to identify significant cognitive impairment. [181 words]. Highlights: Conventional bedside tests of visuospatial function lack consistency in delivery and interpretation. The LSD-4 is a novel bedside test of visuospatial ability that is brief, easily interpreted and with high coverage of elderly patients. The LSD-4 has good agreement with conventional visuospatial tests and favourable ability to identify significant cognitive impairment.